Nature of Bonding in Bowl‐Like B36 Cluster Revisited: Concentric (6π+18π) Double Aromaticity and Reason for the Preference of a Hexagonal Hole in a Central Location - Li, Rui; You, Xue‐Rui; Wang, Kang; Zhai, Hua‐Jin (Chemistry, an Asian journal, 2018)
The bowl‐shaped C6v B36 cluster with a central hexagon hole is considered an ideal molecular model for low‐dimensional boron‐based nanosystems. Owing to the electron deficiency of boron, chemical bonding in the B36 cluster is intriguing, complicated, and has remained elusive despite a couple of papers in the literature. Herein, a bonding analysis is given through canonical molecular orbitals (CMOs) and adaptive natural density partitioning (AdNDP), further aided by natural bond orbital (NBO) analysis and orbital composition calculations. The concerted computational data establish the idea of concentric double π aromaticity for the B36 cluster, with inner 6π and outer 18π electron counting, which both conform to the (4n+2) Hückel rule. The updated bonding picture differs from existing knowledge of the system. A refined bonding model is also proposed for coronene, of which the B36 cluster is an inorganic analogue. It is further shown that concentric double π aromaticity in the B36 cluster is retained and spatially fixed, irrespective of the migration of the hexagonal hole; the latter process changes the system energetically. The hexagonal hole is a destabilizing factor for σ/π CMOs. The central hexagon hole affects substantially fewer CMOs, thus making the bowl‐shaped C6v B36 cluster the global minimum. Bonding in boron bowls: The bowl‐shaped C6v B36 cluster is shown to possess inner 6π and outer 18π aromatic subsystems (see figure). This bonding pattern is retained and spatially fixed, irrespective of the migration of the hexagonal hole. Analysis also sheds crucial light on the reason why the hexagonal hole in B36 prefers to be positioned in the center of the bowl.